The impact of flexible working hours towards employee's productivity at Felda D'saji Sdn. Bhd., Kuala Lumpur / Assma Nuraina Anuwar - Anuwar, Assma Nuraina (Faculty of Business and Management, 2018)
The purpose is to study the impact of flexible working hours towards employee's productivity at Felda D'Saji Sdn. Bhd., Kuala Lumpur. This correlational research used a cluster sampling technique and the sample size was determined using the Krejcie and Morgan (1970) sample size table Questionnaires were distributed to 56 employees and the accepted questionnaires was 56 sets with 100%. The questionnaires were analysed using SPSS Version 23.0 to determine the result. The higher gender of the respondents for this study was female. Most of respondents at Felda D'Saji Sdn. Bhd. aged less than 30 years old and 30 - 39 years old. It has been identified that the respondents answered the questionnaire were the majority of employees with married status. However, the majority of employees in this organization had Sijil Pelajaran Malaysia (SPM) for their highest education level and working experience for 10-15 years. The finding shows that there was a high impact of flexible working hours towards employee's productivity. In addition, it also shows a significant relationship between flexible working hours towards employee's productivity. It is recommended that organization should adopt the flexible working hours (FWH) programs. The future research can conduct this study by extend or increase the sample size so that the findings shall be more accurate. Hence, future researchers may use different method of sampling for data collection.